Aspectos técnicos, operativos y ambientales en los sistemas de abastecimiento de agua potable en municipios con nivel de complejidad medio: Un estudio de caso - Lara, Yefer Asprilla; Martínez Amado, Maira A.; Mora Naranjo, Laura A. (Tecnogestión: Una mirada al ambiente, 2015)
The availability of water resources is undoubtedly one of the most complex current problems facing many countries of the world, in which intervene diverse factors that are beyond the growing demand of water to the consumption such as: population growth, pollution and overexploitation of water resources that generate increasingly difficulties in quality and continuity of water service in many municipalities in our country. This article depicts technical, operational, and environmental aspects of the supplying of drinking water system of Viotá municipality in Cundinamarca department, which is exposed to suffering difficulties in the service delivery if necessary steps are not taken for improving the performing. This case study permitted identifies each one of the structures, components, and elements used since the capturing of water to the users addresses water service